Bacterial Cellulose Production from Agro-Industrial Waste for Food-Grade Edible Coating: A Systematic Review - Divya S; Chandrika S Tantry; Manjunatha Bukkambudhi Krishnaswamy; Mahanthesh Kumar G T; Vidya Shimoga Muddappa (The Bioscan, 2026)
Food losses after harvesting amounting to 1.3 billion tonnes each year pose a threat to achieving the United Nations Sustainable Development Goals, including SDG 2 (Zero Hunger), SDG 12 (Responsible Consumption and Production), and SDG 9 (Industry, Innovation and Infrastructure). Bacterial cellulose (BC) is a purified and crystallized extracellular polysaccharide with excellent mechanical properties and barrier behavior applicable as a food coating. Despite these benefits, wider application of BC in the food industry remains limited due to high production costs in Hestrin-Schramm medium cultivation technology. This paper addresses a research gap in the bibliography on BC production optimization for edible coating development, focusing not only on production yield but on other relevant aspects. Bibliometric analysis based on the Scopus database of indexed papers from 2014 to 2026 using the Bibliometrix R-package was performed. Through narrative synthesis based on a novel production-property-performance (PPP) framework, this research proves that fermentation conditions during the initial phase of BC production play a key role in determining coating- related properties such as crystallinity index, moisture permeation rate, and film-forming ability. Ideal fermentation conditions include Komagataeibacter bacteria, stationary culture, fruit- derived waste material, a temperature of 28–30°C, pH 5.5–6.5, yielding crystallinity indices of 70–90%.